Three-dimensional tracking and analysis of ion channel signals across dendritic arbors - Ginger, Melanie; Broser, Philip; Frick, Andreas (Frontiers in Neural Circuits, 2013)
Most neuron types possess elaborate dendritic arbors that receive and integrate excitatory and inhibitory inputs from numerous other neurons to give rise to cell-type specific firing patterns. The computational properties of these dendrites are therefore crucial for neuronal information processing, and are strongly determined by the expression of many types of voltage-gated ion channels in their membrane. The dendritic distribution patterns of these ion channels are characteristic for each ion channel type, are dependent on the neuronal identity, and can be modified in a plastic or pathophysiological manner. We present a method that enables us to semi-automatically map and quantify in 3D the expression levels of specific ion channel types across the entire dendritic arbor. To achieve this, standard immunohistochemistry was combined with reconstruction and quantification procedures for the localization and relative distribution of ion channels with respect to dendritic morphology. This method can, in principle, be applied to any fluorescent signal, including fluorescently tagged membrane proteins, RNAs or intracellular signalling molecules.